Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Naskapi (0908) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Policy Brief : Mental Health and Suicide Prevention - Nunavik, Quebec - Youth for Youth Québec (Y4Y Québec)
In recent years, communities across Nunavik have received attention for other reasons than their young demographic: a growing suicide epidemic. In fact, remote and northern communities in Canada have consitently experienced the most significant effects of suicide in the country, with general incidence rates staggering at ten times the national average and as much as 24 times the national average (National Observer, 2019) for Inuit youth across Nunavik. Although there was a window between 2009 and 2013 when suicide was on the decline, the tendency has been consistently increasing for the past seven years (CBC, 2018).